Religious fasting: an alternative approach to improve hyperlipidaemia - Khattak, Muhammad Muzaffar Ali Khan; Abu Bakar, Ibrahim; Yeim, Liyana (Emerald Group Publishing Ltd., 2012)
Purpose: The purpose of this paper is to evaluate the effect of fasting on blood lipid profile in fasting obese and non-obese subjects. Design/methodology/approach: Male and female subjects from the International Islamic University, Malaysia (IIUM), Kuantan Campus were assessed for body compositional changes during Ramadan fasting. In total, 25 males and females volunteered to participate in this study in the holy month of Ramadan. The mean age of the volunteers was 26.5±5.86 years and the age range was 21-45 years. The age, weight and height of the volunteers were recorded on day 1 of Ramadan and weight was also recorded on day 21. The volunteers were asked for donation of blood samples on days 1, 7, 14 and 21 of the Ramadan. The blood serum was separated and stored at -20°C immediately after each collection. The serum samples stored at -20°C were analyzed for serum glucose and lipid profile. The analysis of serum lipid profile was performed with the help of clinical kits from Bayer Health Care using Bayer Express Plus Clinical analyzer. The serum was used for the estimation of total cholesterol (TC), HDL-cholesterol (HDL-c) and triglycerides (TG) concentrations using kit reagents from M/s Bayer Diagnostics, whereas low density lipoprotein cholesterol (LDL-c) was determined by calculation. The statistics were performed using MINITAB statistical software (release 8.2). Findings: The serum triglyceride concentration was significantly reduced and the reduction was 17.48 percent from day 1-21. The serum TC concentration also reduced from day 1-21 and the reduction was 15.93 percent. The serum LDL-c concentration also significantly reduced from day 1-21 and the reduction was 21.67 percent. The serum HDL-c concentration decreased in the first weak and second week but an improving trend was observed on day 21 of the Ramadan. Research limitations/implications: This study was not a controlled one and was conducted on free-living individuals and therefore there is need to have controlled or adjusted physical activities studies in fasting individuals. It is always difficult to conduct experiment on human beings in the metabolic area. Furthermore, in this study it was not possible since it was a religious fasting. Another limitation is that the size of the sample was smaller than is advisable for this kind of study. However, the results were confirmed in the following month of Ramadan, as described in the paper. Originality/value: The paper takes into consideration the effect of Ramadan fasting on blood lipid profile, which has ever been studied in obese individuals.